APPLYING TRAJECTORY TRACKING AND POSITIONING TECHNIQUES FOR REAL-TIME AUTONOMOUS FLIGHT PERFORMANCE ASSESSMENT OF UAV SYSTEMS - Mostafa S.A.; Mustapha A.; Ramli A.A.; Darman R.; Zeebaree S.R.M.; Mohammed M.A.; Gunasekaran S.S.; Ibrahim D.A. (Science Press, 2023)
Aircraft detection; Real time systems; Unmanned aerial vehicles (UAV); Vehicle performance; Aerial vehicle; Autonomous system; Performance; Performance-based assessment; Positioning techniques; Real- time; Tracking techniques; Trajectory tracking technique; Trajectory-tracking; Unmanned aerial vehicle; Antennas